Some implications of a sexual cycle in theileria - Irvin, A.D.; Boarer, C.D.H. (Cambridge University Press, 1980)
Recent microscopic studies of Theilerial parasites in. ticks appear to provide convincing evidence for a sexual cycle for these parasites. This evidence would remove most of the objections to placing piroplasms in the same class as malarial and coccidial parasites. It is suggested, therefore, that the class Piroplasmasida (Piroplasmea) be abolished and that piroplasms be located in a sub-order Piroplasmorina alongside Haemosporina within the class Sporozoa (Teleospora).If the close relationship of Theilerial and malarial parasites is correct then by analogy meiotic or reduction division of Theileria probably occurs during sporogony in the tick salivary gland acinar cells. This means that all bovine stages are haploid. If these can be cloned and characterized by isoenzyme or drug resistance markers, then genetic recombinant studies, similar to those performed with malarial and coccidial parasites, could be conducted.The potential of genetic recombination greatly increases the scope of the parasite for developing new variants. This potential is greatest in areas where there is a variety of tick and host species which apply different types of selection pressure to parasites. Atypical strains of Theileria are usually isolated from such areas, and although the characteristics of these strains may not be expressed in the wild, unnatural selection by laboratory passage may reveal their presence. The apparent lability of such strains may simply be cloning of different genetic recombinants.If different strains can be cloned and characterized it may be possible by genetic recombination techniques to develop new clones which retain desired characters for use as avirulent protective vaccines, but from which undesirable characters have been eliminated.